2019
DOI: 10.1155/2019/6073019
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ovarian Cancer Cell Cytotoxic Drug Resistance Phenotype with Xanthium strumarium L. Extract

Abstract: Emerging drugs aim at targeting the genomic integrity and replication machinery in ovarian cancer. While the antiproliferative activity of Xanthium strumarium L. extract (XFC), a traditional herbal medicine, is believed to alter the mitotic apparatus of Chinese hamster ovary epithelial cells, its capacity to target and overcome the chemoresistance phenotype in ovarian cancer is unknown. Among the cancer cell lines tested, we found that the best proliferation inhibitory effect for XFC was against ovarian cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…MDA-MB-231 cells were seeded into 6-well tissue culture dishes and grown to nearly confluent cell monolayers. Then, a linear wound was generated in the monolayer with a sterile 200 μL pipette tip creating a cell-free area [ 62 ]. Cultures were gently washed with the growth medium to remove loose cells.…”
Section: Methodsmentioning
confidence: 99%
“…MDA-MB-231 cells were seeded into 6-well tissue culture dishes and grown to nearly confluent cell monolayers. Then, a linear wound was generated in the monolayer with a sterile 200 μL pipette tip creating a cell-free area [ 62 ]. Cultures were gently washed with the growth medium to remove loose cells.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in an ex vivo model, administration of the extracts inhibited tumoral growth and induced apoptosis by suppressing the PI3K/AKT/mTOR signaling pathways in the cancerous cells [49]. Comparable IC 50 values were also reported for other cancerous cell types, including colorectal adenocarcinomas (HT-29 and C2BBe-1), breast adenocarcinomas (MDA-MB-231 and MCF-7), and ovarian carcinomas (SKOV-3 and ES-2) after treatment with an ethanolic extract of X. strumarium L. leaves [50]. Higher cytotoxicity was reported in Chinese hamster ovary cells after treatment with the whole extract of the aerial parts of X. strumarium L. The calculated IC 50 in this latter case was 20.5 µg/mL [51].…”
Section: Discussionmentioning
confidence: 69%
“…Health professionals have different opinions about treating OC. Francisco Fernandez et al [ 20 ] believed that invigorating the spleen and tonifying the kidney could improve the fatigue symptoms of OC patients. Tao et al reported [ 21 ] that the treatment of OC should be based on disease differentiation, constitution differentiation, and combination of disease differentiation and syndrome differentiation.…”
Section: Discussionmentioning
confidence: 99%